Triage education in rural remote settings: A scoping review. (March 2019) - Hardy, Amber; Calleja, Pauline
Highlights: A scoping review that demonstrates the need for more research into rural and Graduate Registered Nurse's triaging. Benchmarking required for triage training efficacy. Global shift towards national standardised five-tier triage scales. Need for national standardised triage education. Abstract: Background: Triage is a complex nursing task to prioritise patient care, based on acuity. Triage decisions can affect patient safety and must employ critical thinking. Graduate registered nurses are expected to triage in rural facilities, which is in contrast to current guidelines. The purpose of this review was; to discover how effective education support programs were in developing clinical decision-making skills for graduates at triage; and to determine what is known about triage education support programs for graduate or novice registered nurses undertaking triage in rural and remote settings. Method: A scoping review was undertaken to identify and analyse primary research articles following PRISMA guidelines, sourced from four electronic databases. Results: 6158 retrieved articles were found, after duplicate removal and screening against inclusion/exclusion criteria; fourteen articles were included. Themes included 'variability of triage accuracy and assessment'; 'education qualifications and experience'; and 'training and supervision'. Conclusion: This review demonstrates significant gaps in the literature reporting on this topic area, particularly in the rural context. Common recommendations include standardised triage education strategies, and strategies that account for differences in resourcing levels. Further research is required to attempt to link education strategies in rural contexts to acceptable triage outcomes like triage accuracy.